Energy commerce and business economics: A review of trends, challenges, and opportunities - Solaiyammal Pandi; Josephin Arulmozhi S; Gurupandi M; Ramaraj , Ramachandran (Maejo International Journal of Energy and Environmental Communication, 2025)
The energy industry globally is being reshaped by the influences of going green, reducing reliance on large utilities, and increased technology. These shifts prove that energy commerce and business economics greatly affect the changes in how, where, and what energy is used. Now that energy transactions are digital, they run smoothly, and the fairness of competition is boosted. Digitalization also helps businesses improve and achieve growth. The growth of this sector has come from steps like creating the market, dealing with issues in the market, supporting creative business ideas, fueling digital change, lessening regulations, and supporting consumer interests. Whenever the government is involved in projects, the team should pay special attention to the financial aspect, regulations, and sustainability during planning and implementation. Changes in energy markets are determined by rules set by regulators and the way they handle carbon trading. Thanks to AI, blockchains, and FinTech, there are now more opportunities for providing and trading energy. Still, the industry must deal with issues brought on by changes in regulations, swings in the market, and cybersecurity dangers. Soon, using Energy-as-a-Service, environmental, social, and corporate governance (ESG) finance, and merging AI, big data, and circular economy principles will make a big impact on sustainable development. Consequently, this research review demonstrates the value of combining technology, reorganizing systems, and developing economic approaches to drive the changes in energy commerce.